Selection for morphology, gaits and functional traits in Lusitano horses: I. Genetic parameter estimates. - Vicente, António (2014)
Genetic parameters were estimated for morphology, gaits and functional traits in Lusitano horses by uni- and multivariate animal models. Morphological traits considered in the analyses were partial scores attributed to up to 18,076 horses at the time of registration in the studbook and included head and neck, shoulder and withers, chest and thorax, back and loin, croup, legs and overall impression, plus a final score computed by summing the partial morphological scores and the gaits score. The functional traits considered were the scores obtained in the dressage and maneability trials of working equitation (WE, about 1500 records by 200 horses), and classical dressage (12,131 records by 759 horses). The heritability (h2) estimates for all partial morphological scores ranged between 0.12 and 0.18, except for legs (0.07). The h2 for final score, height at withers and gaits was 0.18, 0.61 and 0.17, respectively, while for WE dressage trial and classical dressage it was 0.32 and for WE maneability trial it was 0.18. The genetic correlations (rG) of final score with the different partial scores were generally high (0.56–0.95), while among partial components of morphology they were positive but widely different (0.08–0.77). With the exception of legs, rG between morphology/gaits and functional traits were positive, with a stronger relationship between morphological traits and performance in WE dressage trial (rG between 0.36 and 0.56) when compared with performance in maneability trial or classical dressage. Height at withers had a rG of 0.40 with performance in classical dressage, but lower rG(0.06 and −0.10) with WE trials. Final score and overall impression had moderate to strong genetic relationships with functional traits, especially with WE dressage trial, while gaits had a strong rG with performance in all the disciplines (0.60–0.72). Indirect selection for morphology/gaits to improve functionality was assessed, by selecting for final score or a combined index of partial scores. Compared to direct selection for functionality, selection for final score or an index combining partial morphological scores would be less effective, resulting in accuracies of, respectively, 0.28 and 0.37 for WE dressage trial, 0.14 and 0.38 for WE maneability trial and 0.22 and 0.39 for classical dressage. Thus, an index combining all partial morphological scores would be better than selection for overall final score, but its relative efficiency compared to direct selection would be about 0.7 in WE dressage trial and classical dressage, and 0.9 in WE maneability trial. Lusitano horses maintain considerable levels of genetic variability, and selection for both morphology and functionality should be effective. The favorable genetic relationships existing between morphology and performance indicate that morphology/gaits traits can play an important role in a two-stage selection program, contributing to enhance selection response when the genetic improvement of working equitation or classical dressage is intended.